EP544 Saten III - splitting adjuvant treatment into subgroups of stage III endometrioid endometrial cancers: an international, multicenter study. (1st November 2019) - Kahramanoglu, I; Meydanli, MM; Taranenka, S; Ayhan, A; Salman, C; Sanci, M; Demirkiran, F; Ortac, F; Haidopoulos, D; Sukhin, V; Kaidarova, D; Stepanyan, A; et al.
Abstract : Introduction/Background: The primary aim was to determine whether different adjuvant treatment modalities (CT, RT, and CRT) improve survival outcomes in stage III endometrioid EC patients based on the specific sub-stage of the disease. The secondary aim was to assess the prognostic factors in stage III endometrioid EC. Methodology: SATEN III was a retrospective study involving 13 centers from 10 countries. Patients who had been operated on between 1998 and 2018 and diagnosed with stage III endometrioid EC were analyzed. Results: A total of 990 women overall were identified; 317 with stage IIIA, 18 with stage IIIB, and 655 with stage IIIC diseases. The median follow-up was 42 months. The 5-year DFS of patients with stage III EC by adjuvant treatment modality was 68.5% for radiotherapy (RT), 54.6% for chemotherapy (CT), and 69.4% for chemoradiation (CRT) (p=0.11). The 5-year OS for those patients was 75.6% for RT, 75% for CT, and 80.7% for CRT (p=0.48). Negative peritoneal cytology (Hazard ratio [HR]: 0.45, 95% confidence interval [CI]: 0.23–0.86; p=0.02) and performance of lymphadenectomy (HR: 0.33, 95% CI: 0.16–0.77, p=0.001) were independent predictors for improved OS for stage IIIA EC. Independent prognostic factors for better OS for stage IIIC disease were age <60 (HR: 0.50, 95%CI: 0.36–0.69, p<0.001), grade 1 or 2 disease (HR: 0.59, 95% CI: 0.37–0.94, p=0.014; and HR: 0.65, 95% CI: 0.46–0.91, p=0.014, respectively), absence of cervical stromal involvement (HR: 063, 95% CI: 0.46–0.86, p=0.004) and performance of para-aortic lymphadenectomy (HR: 0.52, 95% CI: 0.35–0.72, p<0.001). Conclusion: Although not statistically significant, CRT seemed to be a better adjuvant treatment option for stage IIIA endometrioid EC. However, we were not able to show the superiority of adjuvant CRT in stage IIIC endometrioid EC.Systematic lymphadenectomy seemed to improve survival outcomes in stage III endometrioid EC. Disclosure: Nothing to disclose.